Los retos de la formación de comunicadores en la era tecnológica. - Cadavid Bringe, Amparo (Chasqui (13901079), 2010)
The article examines challenges facing academic institutions as they consider how to incorporate rapidly changing information and communications technologies into their communications and media programs. It notes challenges to teaching posed by the gap in technological knowledge between teachers and students. The article further describes potential drawbacks of over-reliance on computers as educational tools, including the possible diminished ability of students to analyze long texts, the tendency to resort to computers for the performance of mathematical calculations, and potential limits on the development of creative thinking skills.